Designing an Integrated Blockchain-Based Waqf Governance Model for Indonesia: Delphi-Likert Approach - Syahrul Ihsan; Syamsuri (Journal of Islamic Economics and Finance Studies, 2025)
Waqf experiences significant developments every year. At the same time, transparency and accountability remain crucial challenges related to waqf in Indonesia. This study aims to identify the key characteristics of blockchain-based waqf governance and propose a relevant governance model in the Indonesian. The digitalization of waqf through blockchain technology offers significant opportunities to enhance transparency and accountability in waqf governance in Indonesia. To identify characteristics and propose a relevant model in the Indonesian context, a Delphi-Likert method was used, involving eleven respondents comprising academics, regulators, and practitioners in the waqf and blockchain fields. The results indicate that the most important aspects for blockchain integration are strengthening the database system, collecting, and managing waqf. The majority of respondents believe blockchain needs to be implemented immediately, with a preference for hybrid and public networks. Furthermore, a limited open ecosystem is seen as the most realistic form of governance because it balances the need for transparency with the protection of the institution's internal data. This study contributes theoretically to the literature on Islamic social finance and practically provides recommendations for an integrated governance model for waqf institutions in Indonesia.   Wakaf mengalami perkembangan yang signifikan setiap tahunnya. Pada waktu yang sama, permasalahan transparansi dan akuntabilitas masih menjadi tantangan krusial terkait wakaf di Indonesia. Penelitian ini bertujuan mengidentifikasi karakteristik utama tata kelola wakaf berbasis blockchain dan mengusulkan model tata kelola yang relevan dalam konteks Indonesia. Digitalisasi wakaf melalui teknologi blockchain menawarkan peluang besar untuk meningkatkan transparansi dan akuntabilitas tata kelola wakaf di Indonesia. Untuk menemukan karakteristik dan usulan model yang relevan dalam konteks Indonesia, maka pendekatan Delphi-Likert dengan melibatkan sebelas responden terdiri dari akademisi, regulator, dan praktisi pada bidang wakaf dan blockchain. Hasil penelitian menunjukkan bahwa aspek yang paling penting untuk diintegrasikan dengan blockchain adalah penguatan sistem database, penghimpunan, dan pengelolaan wakaf. Mayoritas responden menilai bahwa blockchain perlu diimplementasikan segera dengan preferensi pada jaringan hybrid dan publik. Selain itu, ekosistem terbuka terbatas dipandang sebagai bentuk tata kelola paling realistis karena mampu menyeimbangkan kebutuhan transparansi dengan perlindungan data internal lembaga. Penelitian ini berkontribusi secara teoritis dalam memperkaya literatur keuangan sosial Islam dan secara praktis memberikan rekomendasi model tata kelola terintegrasi bagi Lembaga wakaf di Indonesia.